2016
DOI: 10.1007/s10792-016-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolates and antibiotic susceptibilities of endophthalmitis in postcataract surgery: a 12-year review of culture-proven cases

Abstract: The purpose of this study was to investigate the spectrum of organisms causing endophthalmitis after cataract surgery in a tertiary medical center in Taiwan and the antibiotic susceptibilities. This was a retrospective case series study. Patients with endophthalmitis after cataract surgery from January 2004 to July 2015 were reviewed. The outcome measures included the identification of isolates, antibiotic susceptibilities, and final visual outcomes. Twenty-one organisms were isolated from 19 cases. The most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…Similar to prior studies, vancomycin was effective against all 45 isolates in this study, and it remains one of the most effective empiric treatments for endophthalmitis [5,6,9,10,24]. However, delafloxacin has the benefit of wider microbial coverage including Gram-negative organisms like P. aeruginosa, anaerobes, and atypical infections [25,26].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to prior studies, vancomycin was effective against all 45 isolates in this study, and it remains one of the most effective empiric treatments for endophthalmitis [5,6,9,10,24]. However, delafloxacin has the benefit of wider microbial coverage including Gram-negative organisms like P. aeruginosa, anaerobes, and atypical infections [25,26].…”
Section: Discussionsupporting
confidence: 82%
“…Of 45 total isolates identified between 2014 and 2018, 13% (6) were methicillin-resistant S. aureus (MRSA), 9% (4) were methicillin-sensitive S. aureus (MSSA), 53% (24) were methicillin-resistant S. epidermidis (MRSE), and 24% (11) were methicillin-sensitive S. epidermidis (MSSE, see Table 1). Among the fluoroquinolones, resistance rates across all organisms were 60% for levofloxacin, 50% for moxifloxacin, and 12% for delafloxacin (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the series was predominantly Enterococcus (38%). 6 Although vancomycin resistant organisms have been described post-cataract surgery, they remain rare. 7 The use of intracameral antibiotics at the time of cataract surgery (vancomycin, cephalosporins, or fluoroquinolones) is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to South Korea, the incidence of Enterococcus spp. has been increasing in Sweden, Japan, and Taiwan [4,7,8,21]. A recent report in Taiwan showed that Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Enterococcus spp. have emerged as a major causative strain of PE in Sweden, Korea, and Taiwan [4,7,8]. The reason underlying the increase of Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%